STUDY OF GEOTHERMAL WATER INTRUSION DUE TO GROUNDWATER EXPLOITATION IN THE PUEBLA VALLEY AQUIFER SYSTEM, MEXICO - Flores-Márquez E.L.; Jiménez-Suárez G.; Martínez-Serrano R.G.; Chávez R.E.; Pérez D.S. (My University, 2006)
Significant intrusion of geothermal water into fresh groundwater takes place in the Puebla Valley aquifer system, Mexico. The decline in the potentiometric surface due to the overexploitation of the groundwater induces this intrusion. This hydrological system comprises three aquifers located in Plio-Quaternary volcanic sediments and Mesozoic calcareous rocks. The hydraulic balance of the aquifer shows that the annual output exceeds the natural inputs by 12 million m3. Between 1973 and 2002, a drop in the potentiometric surface, with an 80 m cone of depression, was identified in a 5-km-wide area located southwest of the city of Puebla. Chemical analyses performed on water samples since 1990 have shown an increase in total dissolved solids (TDS) of more than 500 mg/L, coinciding with the region showing a cone of depression in the potentiometric surface. A three-dimensional flow and transport model, based on the hydrogeological and geophysical studies, was computed by using the MODFLOW and MT3D software. This model reproduces the evolution of the aquifer system during the last 30 years and predicts for 2010 an additional drawdown in the potentiometric surface of 15 m, and an increase in the geothermal water intrusion.
Keywords: SIMULATION; GROUNDWATER FLOW; TRANSPORT; GEOTHERMAL WATER INTRUSION; PUEBLA AQUIFER; Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная